2019
DOI: 10.1200/jco.2019.37.15_suppl.e20565
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in combination with immune checkpoint inhibitors for the first-line treatment of patients with advanced non-small cell lung cancer: A systematic review and literature-based meta-analysis.

Abstract: e20565 Background: Checkpoint inhibitors plus platinum-based chemotherapy have shown superiority compared to chemotherapy alone as first-line therapy in advanced non–small cell lung carcinoma (NSCLC),To evaluate the relative benefit in term of Overall Survival (OS) and Progression-free Survival (PFS) of checkpoint inhibitors plus chemotherapy versus chemotherapy alone, overall and in subgroups defined by PDL1 expression we have performed a meta-analysis Methods: This meta-analysis searched PubMed and checked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…In this case, the immunotherapy plus chemotherapy cohort demonstrated a superior anti-tumor effects for the entire duration of the follow-up [ 136 ]. Subsequent studies confirmed these initial findings [ 137 ], as also clearly shown in a recently published meta-analysis [ 138 ]. Indeed, Addeo et al collected the data from several randomized clinical trials in which chemotherapy was administered with ICIs as first-line treatment for metastatic NSCLC patients.…”
Section: Possible Tumor-related Mechanisms Of Hpdsupporting
confidence: 69%
See 2 more Smart Citations
“…In this case, the immunotherapy plus chemotherapy cohort demonstrated a superior anti-tumor effects for the entire duration of the follow-up [ 136 ]. Subsequent studies confirmed these initial findings [ 137 ], as also clearly shown in a recently published meta-analysis [ 138 ]. Indeed, Addeo et al collected the data from several randomized clinical trials in which chemotherapy was administered with ICIs as first-line treatment for metastatic NSCLC patients.…”
Section: Possible Tumor-related Mechanisms Of Hpdsupporting
confidence: 69%
“…The Authors compared the PFS and OS of the chemotherapy alone group versus the chemotherapy plus immunotherapy arm. They found that in all considered clinical trials the combination of chemo/immunotherapy conferred an advantage in terms of OS and PFS compared to chemotherapy alone [ 138 ]. Apparently, no signs of HPD were detected in these trials.…”
Section: Possible Tumor-related Mechanisms Of Hpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Representing 80-85% of all cases of lung cancer, non-smallcell lung cancer (NSCLC) is one of the leading causes of cancer-related deaths worldwide [1]. Over the course of the last decade, the prognosis improved drastically, in large part thanks to the advent of immune checkpoint inhibitors (ICIs) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, several studies have shown that only a subset of patients could benefit from this therapeutic protocol, such as patients with wild-type EGFR or negative ALK rearrangements (40,41). Moreover, in different PD-L1 expression subgroups, the benefit in OS and PFS is mixed (42).…”
mentioning
confidence: 99%